Exploring the meaning of using VOD (video on demand) Didik TV as a video repository system for PDP (teaching and learning): a need analysis study - Mohd Rokhani, Zaiemilia; Ab Jalil, Habibah; Azmi Murad, Masrah Azrifah; Nasharuddin, Nurul Amelina (Human Resource Management Academic Research Society, 2024)
For the purpose of framework or model development research, needs analysis is conducted to ensure that the product produced meets the needs of users. This study was carried out to identify the requirements for the development of the framework and elements of the video repository system for PdP, which is the basis for the production of products in the form of application systems. This needs analysis study is based on the phenomenon of the use of Didik TV by teachers since the Covid-19 pandemic. When Covid-19 hit, the Malaysian Ministry of Education (MOE) ordered that learning sessions continue with the PdPR (Teaching and Learning from Home) method. The MOE has created a special Education TV broadcast called Didik TV on the NTV7 channel on February 17, 2021 to support the PdPR session. This study uses an in-depth semi-structured interview approach to explore the experiences, challenges and suggestions for improvement by experienced teachers using Didik TV. Purposive sampling technique was used in this study to select five (5) teachers. Qualitative data from the results of interviews with teachers were categorized and analyzed and interpreted and found three (3) main themes, namely: (1) Didik TV is practical to use, (2) the inefficiency of Didik TV in delivering content is a challenge for teachers and students, and (3) a proposal for the development of an intelligent video repository system for PdP. Apart from the three themes obtained, the teacher's suggestions have also produced a list of elements that can be used as a basis for design and development in the next phase of the study. This study has the potential to be used as a recommendation and guide to develop a smart video repository system for the authorities in the education system to realize the implementation of digital learning in Malaysia.